What the Future Holds for Solid-State Memory. - Strauss, Karin; Burger, Doug (Computer (00189162), 2014)
The memory industry faces significant disruption due to challenges related to scaling. Future memory systems will have more heterogeneity at individual levels of the hierarchy, with management support from multiple layers across the stack.